Plant-microbe interactions to probe regulation of plant carbon metabolism - Sonnewald, Uwe; et al. (Journal of Plant Physiology, 2006)
Plant growth and development is dependent on coordinated assimilate production, distribution and allocation. Application of biochemical and molecular techniques substantially contributed to a better understanding of these processes, although the underlying regulatory mechanisms are still not fully elucidated and attempts to improve crop yield by modulating carbon partitioning were only partially successful.. Plant pathogens also interfere with source-sink interaction. To this end they have evolved a wide range of sophisticated strategies to allow their systemic spread, suppression of plant defence and induction of sink function to support nutrient acquisition for their growth. Studying compatible interactions of plants and pathogens like viruses, bacteria and fungi can be exploited to investigate different levels of source-sink regulation. The identification of microbial factors and their host targets involved in regulation of plant primary metabolism may allow developing novel strategies to increase crop yield. Here we will. discuss recent studies on plant-microbe interactions aimed at elucidating mechanisms of compatibility. (c) 2005 Elsevier GmbH. All rights reserved.
Keywords: plant-microbe interaction; sink-source regutation; cell wall-invertase